Peningkatan Kemampuan Keaksaraan Awal Menggunakan Media Roda Pintar Di Paud Kasih Ibu - Eli Daryati; Mimpira Haryono; Rohayu Fadilla (Early Childhood Research and Practice, 2026)
This study was motivated by the low early literacy skills of children at PAUD Kasih Ibu, particularly regarding recognizing letter symbols, articulating letter sounds, and matching letters with images. The study aimed to enhance children's early literacy skills through the use of the "Smart Wheel" (*roda pintar*) learning aid. A Classroom Action Research (CAR) design was employed, conducted over two cycles; each cycle comprised the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 12 children. The results indicate that the use of the Smart Wheel effectively improved the children's early literacy skills. In Cycle I, Meeting 1, the achievement rate was 36.45%, falling into the "Beginning to Develop" (MB) category. In Cycle I, Meeting 2, this increased to 48.43% (MB category). Subsequently, in Cycle II, Meeting 1, the rate rose to 63.02%, meeting the "Developing as Expected" (BSH) criterion, and in Cycle II, Meeting 2, it reached 80.72%, achieving the "Developing Very Well" (BSB) category. This improvement demonstrates that the Smart Wheel creates an engaging, enjoyable, and interactive learning atmosphere, thereby fostering greater active participation and enthusiasm among the children. Based on these findings, it can be concluded that the Smart Wheel is an effective tool for enhancing the early literacy skills of young children at PAUD Kasih Ibu.